Digital Media as a Form of Electronic Graffiti (e-Graffiti): From Walls to Social Media - Martins, Vanessa; Braga, Adriana; Logan, Robert K. (New Explorations, 2023)
We will explore the thesis that social media are used to achieve many of the same objectives of traditional wall-based graffiti and as such are forms of electronic graffiti that can reach a much larger audience than traditional graffiti scratched or painted on walls, buildings, monuments and other public surfaces. The parallel of graffiti and e-graffiti is that both provide a medium of communication and expression to those without access to the traditional mass me- dia channels of society controlled by the owners (private or governmental) of commercial me- dia outlets. We will focus in this study on the uses of social media that parallel wall-based graf- fiti such as personal aggrandizement, boasting of achievements, protesting, expressing woke culture, political propaganda and protest, hatred, love, and rebellion. We also identify similari- ties and differences between wall-based traditional graffiti and e-graffiti.